Stellar Ages of TESS Stars, Adopting Spectroscopic Data from Gaia GSP-Spec - Elisa Denis; Patrick de Laverny; Andrea Miglio; Alejandra Recio-Blanco; Pedro Alonso Palicio; Josefina Montalban; Carlos Abia (Galaxies)
The Gaia DR3 GSP-spec/TESS (GST) catalog combines asteroseismic data from NASA’s TESS mission with spectroscopic data from ESA’s Gaia mission, and contains about 116,000 Red Clump and Red Giant Branch stars, surpassing previous datasets in size and precision. The Bayesian tool PARAM is used to estimate stellar ages using MESA models for, currently, 30,297 stars. This GST catalog, which includes kinematics and chemical information, is adopted for studying the Milky Way’s structure and evolution, in particular its thin and thick disk components.